Parenting style of parents undergoing substance abuse treatment having adolescent children (12-20 years old) referring to addiction treatment clinics in Bojnurd - Yasaman Jafari; Rezvan Rajabzadeh; Seyed Hamid Hosseini; Mohammad Khorrami; Nazanin Gholizadeh; Malihe Namvar (Elsevier, 2024)
Background: Considering the adverse effect of drug abuse on Parenting, this study was conducted to determine the parenting style of parents undergoing substance abuse treatment who were referred to addiction treatment clinics in Bojnurd in 2021. Methods: The type of cross-sectional study was descriptive-analytical. The sample size was 360 parents with adolescent children (12-20 years old) undergoing substance abuse treatment who were included in the study by simple random sampling. A two-part questionnaire, including personal characteristics questions and Bamrind's parenting style questionnaire, was used to collect information. Data analysis was done using SPSS 23 software with parametric T-test, ANOVA, and non-parametric equivalent tests of Spearman's correlation at a significance level of 0.05. Results: The average score of permissive, authoritarian, and authoritative parenting styles was (16.15±5.92), (18±6.34) and (24.89±7.09) respectively. Men used permissive and authoritarian parenting styles significantly more than women. The people living in the village, compared to the city residents, and the people in the Turkish and Kurdish ethnicities, compared to Fars, significantly used authoritarian parenting style more. People using opioids significantly less preferred the permissive method and the authoritarian method compared to stimulant drug users and simultaneous users of stimulant and opioid drugs. Conclusion: Children of parents with substance abuse disorders are at risk of various adverse consequences, and it seems that inconsistent behavior of parents is an essential cause of this risk; therefore, the need for public education regarding Parenting, especially in addicted parents, is raised.